Respuesta :
Answer:
- [tex]x_1 = -2[/tex].
- [tex]x_2 = 6[/tex].
Assumption: [tex]f(x)[/tex] is defined for all [tex]x\in \mathbb{R}[/tex] (all real values of [tex]x[/tex].)
Step-by-step explanation:
Evaluating [tex]f(x)[/tex] for a root of this function shall give zero.
Equate [tex]f(x)[/tex] and zero [tex]0[/tex] to find the root(s) of [tex]f(x)[/tex].
[tex]f(x) =0[/tex].
[tex](x - 6) \cdot 2 \cdot (x + 2) \cdot 2 = 0[/tex].
Multiply both sides by 1/4:
[tex]\displaystyle (x - 6) \cdot (x + 2) = 0\times\frac{1}{4} = 0[/tex].
[tex]\displaystyle (x - 6) \cdot (x + 2) = 0[/tex].
This polynomial has two factors:
- (x - 6), and
- (x + 2) = (x - (-2)).
Apply the factor theorem:
- The first root (from the factor (x - 6)) will be [tex]x = 6[/tex].
- The second root (from the factor (x - (-2)) will be [tex]x = -2[/tex].
Answer:
X=6 , X = -2
Step-by-step explanation:
For any polynomial given in factorised form , the roots are determined as explained below:
Suppose we have a polynomial
(x-m)(x-n)(x+p)(x-q)
The roots of above polynomial will be m,n,-p, and q
Also if we have same factors more than once , there will be duplicate roots.
Example
(x-m)^2(x-n)(x+p)^2
For above polynomial
There will be total 5 roots . Out of which 2(m and -p) of them will be repeated. x=m , x=n , x =-p
Hence in our problem
The roots of f(x)= (x-6)^2(x+2)^2 are
x=6 And x=-2